L1CAM in human cancer - Altevogt, Peter; Doberstein, Kai; Fogel, Mina (International journal of cancer, 2016)
L1 cell adhesion molecule (L1CAM) is one of the first neural adhesion molecules described with important functions in the development of the nervous system. Subsequent work discovered that L1CAM is expressed in many human cancers and is often associated with bad prognosis. This is most likely due to the motility and invasion promoting function of L1CAM. Here, we describe the path L1CAM has taken from a neural adhesion molecule to a recognized tumor antigen. We summarize the literature on L1CAM expression in cancers and pre-cancerous lesions. We focus on the genetic elements required for its re-expression and highlight preclinical studies for targeted therapy. The data suggest that L1CAM is a valuable diagnostic/prognostic marker and an attractive target for the therapy of several human cancers.
Gesehen am 28.03.2019
Online 24 June 2015